Evaluation of the Mechanical Strength and Cell Adhesion Capacity of POSS Doped PVA/CMC Hernia Patch - Yildirim, Meryem Akkurt; Ozer, Barkin; Turkoglu, Nelisa; Denktas, Cenk (WILEY-V C H VERLAG GMBH, 2024)
Peritoneal adhesion typically occurs in applications such as abdominal, pelvic, and vascular surgery. It is necessary to develop a mechanical barrier to prevent adhesion. In this study, a novel biomaterial as a mechanical barrier is developed by combining polyvinyl alcohol (PVA) and carboxymethyl cellulose (CMC), doped with polyhedral oligomeric silsesquioxane (POSS) to prevent peritoneal adhesion. Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) methods reveal that POSS nanoparticles in the PVA matrix disrupted the intramolecular hydroxyl groups and structure of the crystal region. Electron microscopy (EM) images reveal that high concentrations of POSS (2 wt.%) cause irregular clustering in the composite matrix. As the concentration of POSS increases in the matrix, the degradation of the membranes increases, and protein adhesion decreases. In vitro cytotoxicity tests show a toxic effect on cells for PVA/CMC composite membranes, while on the other hand, the addition of POSS increases cell viability. According to the MMT test the POSS decreases cell adhesion of membranes. When comparing the POSS doped membrane to the undoped PVA/CMC membrane, an increase in the total antioxidant level and a decrease in the total oxidant level is observed. This study introduces a novel biomaterial to prevent peritoneal adhesions and hernia formation. Combining polyvinyl alcohol and carboxymethyl cellulose with polyhedral oligomeric silsesquioxane (POSS) nanoparticles, the membranes demonstrate suitable mechanical strength for hernia patches. Increasing POSS concentration enhances membrane degradation and reduces protein adhesion, indicating potential as an effective physical barrier. image
Keywords: adhesion; biocompatibility; Hernia patch; Poss; POSTOPERATIVE ADHESIONS; PREVENTION; HYDROGEL; HYBRID; GEL; CARBOXYMETHYLCELLULOSE; COMPOSITES; NANOFIBERS; REDUCTION; POLYMER; Biochemistry & Molecular Biology; Materials Science; Polymer Science